Hubungan Tingkat Pengetahuan Dan Sikap Dengan Kepatuhan Minum Obat Pada Pasien Diabetes Melitus Tipe Ii Di Puskesmas Kelapa Gading - Desy Triyani Parinussa; Astrid Astrid; Sofwan Sofwan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Type II diabetes mellitus is a chronic disease that requires long-term treatment, making medication adherence a factor in the success of therapy. This study aims to determine the relationship between knowledge and attitude levels and medication adherence in type II diabetes mellitus patients at the Kelapa Gading Community Health Center. This study was a quantitative, observational, and analytical design using a cross-sectional approach. The sample consisted of 75 respondents selected using simple random sampling. The research instruments used included the Diabetes Knowledge Questionnaire (DKQ-24), the Diabetes Self-Management Education (DSME) attitude questionnaire, and the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed univariately, bivariately using the Spearman-Rho test, and multivariately using logistic regression. The results showed that most respondents had a moderate level of knowledge (81.3%), a positive attitude (81.3%), and low medication adherence (56.0%). Bivariate analysis showed no significant relationship between knowledge and medication adherence (p=0.915), while there was a significant relationship between attitude and medication adherence (p=0.019). Multivariate analysis showed that attitude being the most dominant variable. The conclusion of this study is that attitude plays a stronger role than knowledge in influencing medication adherence in patients with type II diabetes mellitus. patient education should focus on developing positive attitudes and improving knowledge